Preliminary study of fossil freshwater molluscs from the Plio-Pleistocene Kathmandu Basin sediments, central Nepal (Journal of Nepal Geological Society, 2001)
Fossils of freshwater Mollusca from the fluvio-lacustrine sediments of the Kathmandu Basin are collected from localities in the upper part of the Lukundol Formation, of Late Pliocene to Early Pleistocene age, and the Gokarna Formation, of Late Pleistocene age. Despite the temporal differences of the two localities, the dominant molluscan species in each locality are similar. The fossil molluscan fauna in the older Lukundol Formation is entirely composed of prosobranch gastropod shells belonging to the genus Bellamya and opercula of the genus Digoniostoma. The fauna in the younger Gokarna Formation includes similar prosobranch species with addition of one prosobranch species, along with three pulmonate gastropods, an unidentified terrestrial gastropod and a bivalve species. The additional prosobranch species belong to the genus Gabbia, and the pulmonate gastropods are of the genera Lymnaea, Gyraulus, and Planorbis. The only bivalve species belong to the genus Pisidium.In the Lukundol Formation, fossil molluscan shells are abundant but poor in number of species and the assemblage is dominated by lacustrine taxa preferring permanent lentic water body of shallow depth. Conversely, in the Gokarna Formation, species diversity is comparatively higher, with inhabitant of the shallow lacustrine to marginal less stable habitats. The fossil molluscan faunal composition is more similar to the recent fauna that inhabits the warmer southern Terai region of Nepal.